Estudo da vulnerabilidade ambiental do Sistema Aquífero Boa Vista (SABV): uma análise sobre a ótica da expansão do sistema de esgotamento sanitário no perímetro urbano do Município de Boa Vista/RR - Rodrigues, Apoliana de Souza (2018)
The current academic work aims to analyze the environmental vulnerability of Boa Vista Aquifer System (SABV) and its relation to the expansion of the sanitary sewage system in the urban perimeter of Boa vista - RR. The respective survey was conducted from data collected by tubular wells registered in databases from SIAGAS/ CPRM and technical aquics from CAERR. In order to establish its extent of natural vulnerability from SABV, the God method was used which analyzes the groundwater confinement, lithology and depth to the water table. The evolution, description of physical structure and operation from SES were collected together with CAERR’s technical sector. The map of natural vulnerability and contamination detected over 32% of tubular wells inspected and presented medium vulnerability (area which comprises the city’s genesis and the east and northwest ends) and 68% of the current tubular wells illustrated high vulnerability (concentrated in the northwest and southwest portions). The spatial-temporal evolution map of SES highlighted that the first portions of the city assisted by the sanitary sewage services were those regions that had an average vulnerability index, therefore, the portions which its structures were recently implanted or still in its implantation phase and are concentrated in the areas with high degree of vulnerability. It is noticed that the expansion of its sanitary sewage system in the respective area had a positive factor against the vulnerability of groundwater, yet It will eliminate the most rudimentary forms from disposition of its effluents generated by population, moreover, the correct functioning of the whole public structure from sanitary sewage.